The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/nri.2016.31
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of memory T cells in the bone marrow: survival or homeostatic proliferation?

Abstract: Six years ago, Radbruch and colleagues discussed in Nature Reviews Immunology (Organization of immunological memory by bone marrow stroma. Nat. Rev. Immunol. 10, 193-200 (2010)) 1 how distinct stromal cell subsets in the bone marrow can support the lifelong persistence of plasma cells and memory T cells. These authors proposed that the bone marrow might serve as a depot for resting noncirculating memory T cells. Furthermore, they discussed how memory T cells might be maintained in the bone marrow by survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…A single study in humans did use DNA staining and found that an average of <0.1% of memory‐phenotype CD8 T cells were in S‐G 2 /M in the blood of donors with no systemic diseases . The interpretation at that time was that blood‐derived memory CD8 T cells are resting . Our interpretation is instead that the cells in S‐G 2 /M could have been newly activated cells responding to an environmental antigen.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A single study in humans did use DNA staining and found that an average of <0.1% of memory‐phenotype CD8 T cells were in S‐G 2 /M in the blood of donors with no systemic diseases . The interpretation at that time was that blood‐derived memory CD8 T cells are resting . Our interpretation is instead that the cells in S‐G 2 /M could have been newly activated cells responding to an environmental antigen.…”
Section: Discussionmentioning
confidence: 85%
“…36 The interpretation at that time was that blood-derived memory CD8 T cells are resting. 36,38,39 Our interpretation is instead that the cells in S-G 2 /M could have been newly activated cells responding to an environmental antigen. We suggest that the widespread use of our technical approach might prevent incomplete data analysis and/or biased interpretations.…”
Section: Discussionmentioning
confidence: 92%
“…Both cytokines are both important for CD8 + T-cell maintenance, but with a different underlying mechanism: IL-15 is a potent proliferative agent for CD8 + memory T cells [39,40], whereas IL-7 rather induces their survival [41,42]. Whether CD8 + memory T-cell maintenance in the BM depends on proliferation or survival is a matter that is currently heavily debated [3,4,6,[43][44][45][46][47]. This discussion will greatly benefit from conclusive evidence that IL-7 and/or IL-15 produced by CXCL12 high stromal cells support CD8 + T-cell maintenance in the BM, which requires conditional deletion of these cytokines from BM stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the anticipated role of T RM in other tissues—to provide local protection at sites of pathogen entry—such bone-marrow memory T cells (T BM ) are thought to contribute to systemic memory [24]. Interestingly, in many respects the phenotype of T BM resembles that of T RM cells, with relatively high expression of CD69, and low expression of S1P 1 and Klf2 [25,26].…”
Section: Part I: Thinking Kinetically—how Long Is a Memory?mentioning
confidence: 99%